Review on the Principles and Cutting-Edge Methods of Deep Learning Dynamic Pruning and Model Compression Techniques - Zhao, Yongxi (Transactions on Computer Science and Intelligent Systems Research, 2025)
Deep learning models have achieved remarkable success in fields such as computer vision, natural language processing, and speech recognition. However, their massive parameter counts and high computational complexity severely restrict their deployment in resource-constrained scenarios like edge devices and embedded systems. As a core model compression technology, neural network pruning achieves model lightweight while maintaining performance by removing redundant connections, neurons, or filters. Based on research related to neural network pruning and more cutting-edge achievements, this paper systematically sorts out the core principles, method classifications, application scenarios, and future challenges of pruning technology, providing a comprehensive reference for the research and application of pruning technology.